Penile venous malformations in adult and pediatric populations: diagnosic work-up and management strategies - O. B. Zhukov; D. A. Safin (Вестник урологии, 2025)
Introduction. Venous malformation (VM) is a congenital anomaly of venous development that results from a somatic mutation during the embryonic period, leading to local haemodynamic disturbances.Objective. The research aimed to present clinical cases of patients with penile venous malformations.Materials & methods. Detailed data on the diagnosis and treatment of VM affecting the penis in four pediatric patients aged 2, 7, 10, and 15 years and four adult patients aged 18, 20, 28, and 42 years are presented, including comprehensive case reports for three individuals. For diagnostic purposes, the following methods were employed: ultrasonography with colour Doppler mapping, multiparametric magnetic resonance imaging, and computed tomography with intravenous contrast enhancement. The treatment of venous malformation was carried out using puncture sclerotherapy with the administration of bleomycin solution; in cases of generalised form, «Sirolimus» was additionally prescribed.Results. In seven patients, a local form of VM was detected, limited to the spongy body of the urethra. In one patient, a generalised form of VM was observed, affecting the pelvis, gluteal region, right lower limb, and penis. After performing local bleomycin-based sclerotherapy of VM, a disappearance of its manifestations or a significant reduction in the size of VM was noted.Conclusion. VM is a developmental disorder of venous vessels, representing a low-flow malformation that exhibits significant differences in pathogenesis compared to haemangioma and even more so compared to arterial-venous malformation. These differences must be considered during the diagnostic process and the selection of an appropriate management method.